Is it possible to develop a cross-country test of social interaction?. (2nd November 2017) - Berg, Brett; Atler, Karen; Fisher, Anne G
Abstract: Objective: The Evaluation of Social Interaction (ESI) is used in Asia, Australia, North America and Europe. What is considered to be appropriate social interaction, however, differs amongst countries. If social interaction varies, the relative difficulty of the ESI items and types of social exchange also could vary, resulting in differential item functioning (DIF) and test bias in the form of differential test functioning (DTF). Yet, because the ESI scoring criteria are designed to account for culture, the ESI should be free of DIF and DTF. The purpose, therefore, was to determine whether the ESI demonstrates DIF or DTF related to country. Methods: A retrospective, descriptive, cross-sectional study of 9811 participants 2–102 years, 55% female, from 12 countries was conducted using many-facet Rasch analyses. DIF analyses compared paired item and social exchange type values by country against a critical effect size (±0.55 logit). DTF analyses compared paired ESI measures by country to 95% confidence intervals. Results: All paired social exchange types and 98.3% of paired items differed by less than ±0.55 logit. All persons fell within 95% confidence intervals. Conclusions : Minimal DIF resulted in no test bias, supporting the cross-country validity of the ESI.